Pengaruh Budaya Sekolah dan Motivasi Terhadap Interpersonal Citizenship Behaviour Proses Belajar Mengajar Biologi Peserta Didik di SMAN 16 Jakarta - Gusverizon, Afrilisa Nur Rosifa (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
Education is a solution to develop skills and personality as a solution to challenges according to the needs of current and future developments. Not only improve academic ability, but also personality skills. Based on this, it is necessary to address the problem of wise behavior among students in the teaching and learning process of biology in order to increase student motivation. This study aims to determine the effect of school culture and motivation on interpersonal citizenship behavior in the biology teaching and learning process of students at high school. This research was conducted on 70 students at SMAN 16 Jakarta in the odd semester of 2022/2023 using the causal study method and analyzed using path analysis. The results of the calculation of the reliability coefficient of the interpersonal citizenship behavior are 0,904, motivation is 0,917, and school culture is 0,935. The results of this study are the school culture has a direct effect on motivation, motivation has a direct effect on interpersonal citizenship behavior in the biology teaching and learning process, school culture has a direct effect on interpersonal citizenship behavior in the biology teaching and learning process, and school culture has an indirect effect on interpersonal citizenship behavior in the biology teaching and learning process through motivation.